OP0057 Anti-TNFΑ Therapy Targets PKB/C-AKT Induced Resistance of Effector Cells to Suppression in Juvenile Idiopathic Arthritis. (23rd January 2014) - Wehrens, E. J.; Vastert, S. J.; Mijnheer, G.; Meerding, J. M.; Klein, M.; Wulffraat, N. M.; Prakken, B. J.; van Wijk, F.
Abstract : Background: Resistance of effector T cells (Teff) to suppression contributes to disturbed immune regulation in autoimmune disease. Targeting this unresponsiveness to suppression might therefore have beneficial effects in autoimmune inflammation 1 . In juvenile idiopathic arthritis (JIA) we have recently shown that Teff from inflamed joints are refractory to suppression, which was associated with enhanced PKB/c-akt activation in these cells 2 . Objectives: To investigate whether anti-IL-6 and anti-TNFa influence unresponsiveness of Teff to suppression in patients with JIA. Methods: Resistant Teff from the inflamed joints of JIA patients were cultured in the presence of etanercept or anti-IL-6 in vitro and PKB/c-akt activation and responsiveness to suppression was measured. In addition, in vivo effects of TNFa blockade were investigated using peripheral blood samples of patient before and after start of etanercept therapy. Results: In vitro treatment of synovial fluid Teff with anti-IL-6 led to improved Treg mediated suppression of cell proliferation in some, but not all patients. Blocking TNFa with etanercept however clearly enhanced suppression in all samples analyzed. In the presence of etanercept PKB/c-akt activation of Teff was reduced and Teff became more susceptible to TGFb mediated suppression, indicating that anti-TNFa directly targets resistant Teff. This was confirmed by ex vivo data from patients treated with etanercept demonstrating enhanced responsiveness of effector cells to suppression after therapy. Conclusions: This study is the first to show resistance of Teff to suppression as a target of anti-TNFatherapy in arthritis, resulting in improved regulation of inflammatory effector cells. References: Wehrens EJ, Prakken BJ, van WF. T cells out of control-impaired immune regulation in the inflamed joint. Nat.Rev.Rheumatol. Nat Rev Rheumatol. 2012 Sep 18;9(1):34-42. Wehrens EJ, Mijnheer G, Duurland CL et al. Functional human regulatory T cells fail to control autoimmune inflammation due to PKB/c-akt hyperactivation in effector cells. Blood 2011;118:3538-3548. Disclosure of Interest: None Declared